2010
DOI: 10.14295/bds.2007.v10i3.295
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da terapia de reposição hormonal com raloxifeno e risedronato na reparação óssea de ratas com osteopenia

Abstract: O objetivo do estudo foi de analisar radiograficamente os efeitos do risedronato e do cloridrato de raloxifeno na reparação óssea de ratas osteopênicas. Utilizou-se cinqüenta ratas divididas em cinco grupos de 10 animais cada: (I) SHAM, (II) ovariectomizadas (OVZ), (III) OVZ e tratadas com risedronato 1mg/kg/dia, (IV) OVZ e tratadas com raloxifeno 1mg/ kg/dia e (V) OVZ e tratadas com raloxifeno 3mg/kg/dia . Após trinta dias da ovariectomia executaram-se lesões ósseas de 3 mm de ∅?nas tíbias direitas. Após 7 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Reginster et al (2004) showed a decrease in biochemical markers of bone turnover in women with osteoporosis after the use of estrogen. However, estrogen improved bone mineral density of the lumbar spine, femur and spine only by 2-4% (Sousa et al, 2007;Marques & Liberali, 2012). McClung (2005) found increased mineral density by 1.6% in both lumbar spine and total hip, as well as an increase of 1.2% in the femur neck after two years of treatment with raloxifene at a clinical dose of 60 mg per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reginster et al (2004) showed a decrease in biochemical markers of bone turnover in women with osteoporosis after the use of estrogen. However, estrogen improved bone mineral density of the lumbar spine, femur and spine only by 2-4% (Sousa et al, 2007;Marques & Liberali, 2012). McClung (2005) found increased mineral density by 1.6% in both lumbar spine and total hip, as well as an increase of 1.2% in the femur neck after two years of treatment with raloxifene at a clinical dose of 60 mg per day.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological hormone replacement therapies prevent further bone loss, reduce likelihood of future fractures, prevent the onset of cardiovascular disorders, and psychic disorders, resulting from hormone deficiency in postmenopausal women (Sousa, Alves, Rocha, Moraes, & Carvalho, 2007). Besides hormonal treatment, there has been several attempts to increase the effectiveness of estrogens through the selective estrogen receptor modulators.…”
Section: Introductionmentioning
confidence: 99%